Protective effects of a novel drug RC28-E blocking both VEGF and FGF2 on early diabetic rat retina - Yang, Qian-Hui; Zhang, Yan; Jiang, Jing; Wu, Mian-Mian; Han, Qian; Bo, Qi-Yu; Yu, Guang-Wei; Ru, Yu-Sha; Liu, Xun; Huang, Min; Wang, Ling; Zhang, Xiao-Min; et al. (International journal of ophthalmology, 2018)
To investigate protective effects of a novel recombinant decoy receptor drug RC28-E on retinal damage in early diabetic rats. The streptozotocin (STZ)-induced diabetic rats were randomly divided into 6 groups: diabetes mellitus (DM) group (saline, 3 µL/eye); RC28-E at low (0.33 µg/µL, 3 µL), medium (1 µg/µL, 3 µL), and high (3 µg/µL, 3 µL) dose groups; vascular endothelial growth factor (VEGF) Trap group (1 µg/µL, 3 µL); fibroblast growth factor (FGF) Trap group (1 µg/µL, 3 µL). Normal control group was included. At week 1 and 4 following diabetic induction, the rats were intravitreally injected with the corresponding solutions. At week 6 following the induction, apoptosis in retinal vessels was detected by TUNEL staining. Glial fibrillary acidic protein (GFAP) expression was examined by immunofluorescence. Blood-retinal barrier (BRB) breakdown was assessed by Evans blue assay. Ultrastructural changes in choroidal and retinal vessels were analyzed by transmission electron microscopy (TEM). Content of VEGF and FGF proteins in retina was measured by enzyme linked immunosorbent assay (ELISA). The retinal expression of intercellular cell adhesion molecule-1 (ICAM-1), tumor necrosis factor-α (TNF-α), VEGF and FGF genes was examined by quantitative polymerase chain reaction (qPCR). TUNEL staining showed that the aberrantly increased apoptotic cells death in diabetic retinal vascular network was significantly reduced by treatments of medium and high dose RC28-E, VEGF Trap, and FGF Trap (all <0.05), the effects of medium and high dose RC28-E or FGF Trap were greater than VEGF Trap ( <0.01). GFAP staining suggested that reactive gliosis was substantially inhibited in all RC28-E and VEGF Trap groups, but the inhibition in FGF Trap group was not as prominent. Evans blue assay demonstrated that only high dose RC28-E could significantly reduce vascular leakage in early diabetic retina ( <0.01). TEM revealed that the ultrastructures in choroidal and retinal vessels were damaged in early diabetic retina, which was ameliorated to differential extents by each drug. The expression of VEGF and FGF2 proteins was significantly upregulated in early diabetic retina, and normalized by RC28-E at all dosages and by the corresponding Traps. The upregulation of ICAM-1 and TNF-α in diabetic retina was substantially suppressed by RC28-E and positive control drugs. Dual blockade of VEGF and FGF2 by RC28-E generates remarkable protective effects, including anti-apoptosis, anti-gliosis, anti-leakage, and improving ultrastructures and proinflammatory microenvironment, in early diabetic retina, thereby supporting further development of RC28-E into a novel and effective drug to diabetic retinopathy (DR).